Trust Management in the Internet of Vehicles - Mahmood, Adnan (CRC Press LLC, 2023)
The Internet of Vehicles (IoV) is referred to as an efficient and an inevitable convergence of the Internet of Things, intelligent transportation system, edge / fog and cloud computing, and big data